2020
DOI: 10.1186/s12964-020-00557-2
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a-induced M2 polarization of tumor-associated macrophages via IL-10 promotes colorectal cancer progression

Abstract: Background: Tumor-associated macrophages (TAMs) in the tumor microenvironment influence tumor initiation, invasion and metastasis. Several studies have shown that Wnt5a is mainly expressed in the tumor stroma, especially in TAMs. However, whether Wnt5a regulates the polarization and biological function of TAMs in colorectal cancer (CRC) is incompletely understood. Methods: Immunofluorescence staining was performed to detect CD68 and Wnt5a expression in colorectal tissues from patients (63 CRC specimens VS 20 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 56 publications
5
81
0
1
Order By: Relevance
“…Accumulating evidence has elucidated their clinicopathological significance in predicting the outcomes and therapeutic efficacy in cancer patients (18,19). The infiltration of CD8positive T cells and tumor-associated macrophages was reported to facilitate the progression of epithelial gastric cancer (20)(21)(22). In the present study, infiltration levels of CD8-positive T cells and M1 macrophages were significantly higher in the gastric cancer group with high PAFAH1B3 expression.…”
Section: Discussionsupporting
confidence: 52%
“…Accumulating evidence has elucidated their clinicopathological significance in predicting the outcomes and therapeutic efficacy in cancer patients (18,19). The infiltration of CD8positive T cells and tumor-associated macrophages was reported to facilitate the progression of epithelial gastric cancer (20)(21)(22). In the present study, infiltration levels of CD8-positive T cells and M1 macrophages were significantly higher in the gastric cancer group with high PAFAH1B3 expression.…”
Section: Discussionsupporting
confidence: 52%
“…Liu et al showed that a high Wnt5a+CD68+/CD68+ TAMs ratio can be associated with poor prognosis in colorectal cancer patients. Moreover, they revealed that Wnt5a could induce an M2-like polarization of TAMs, promoting tumor growth and metastasis [ 84 ]. It was also demonstrated that TAMs in colorectal cancer are able to promote angiogenesis and metastasis through the secretion of VEGF [ 102 ].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Schistosomiasis may alter the mechanism underlying the development and progression of CRC, leading to changes in its clinicopathological features and prognosis [37]. TAMs may play an important role in this process [38][39][40][41][42]. In this study, we found that the number of TAMs and the proportion of M2 TAMs in schistosomal CRC tissues were much higher than that in non-schistosomal CRC tissues; both differences were significant.…”
Section: Discussionmentioning
confidence: 51%